Current trends in complete denture education in undergraduate dental colleges of Pakistan - Lone, Muneeb Ahmed; Kumar, Dr. Bharat; Musharraf, Dr. Hira; Lone, Maham Muneeb; Lone, Mohid Abrar; Shaikh, Muhammad Saad; Inayat, Ahsan; Abbas, Muhammad (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the current trends in complete denture education in undergraduate dental colleges. Method: The survey-based study was conducted in April and May 2020 at undergraduate dental colleges of Pakistan, and comprised heads of the Prosthodontics Department at all dental colleges across Pakistan having at least one batch of final year dental students. Data was collected using an online predesigned questionnaire that explored theoretical and practical teaching patterns of complete denture prosthodontics in the undergraduate years, and the materials and practices of students when constructing complete dentures in the clinics. The participants were given the option of choosing more than one option where needed. Data was analysed using SPSS 23. Results: Of the 49 subjects approached, 40(81.6%) returned the forms duly filled; 11(27.5%) from public-sector institutions and 29(72.5%) from the private sector. There were 26(65%) institutions which required that their undergraduate students fabricate 2-4 conventional complete dentures. In all 40(100%) colleges, faculty gave live clinical demonstrations before students fabricated conventional complete dentures in the outpatient departments. Teaching strategy included small group discussions in 25(62.5%) institutions. Green stick 40(100%), zinc oxide eugenol 40(100%) and impression compound 39(97.2%) were the materials of choice for various steps of impression making. In all the 40(100%) institutions, students fabricated conventional complete dentures during their prosthodontics rotation. Immediate, copy and overdentures were constructed by students in 8(20%), 3(7.5%) and 8(20%) institutions, respectively. Conclusions: Majority of the dental schools used similar impression materials and techniques for fabricating conventional complete dentures. Didactic teaching of conventional and unconventional complete dentures was being carried out at a huge majority of the dental institutions studied. Key Words: Current trends, Complete dentures, Undergraduate dental education.